"Chemical Weathering" Exfoliation of Atom‐Thick Transition Metal Dichalcogenides and Their Ultrafast Saturable Absorption Properties. (28th July 2015) - Zhao, Gang; Han, Shuo; Wang, Aizhu; Wu, Yongzhong; Zhao, Mingwen; Wang, Zhengping; Hao, Xiaopeng
Abstract : 2D transition metal dichalcogenides are attracting increased attention because of their excellent electronic and optical properties. Inspired by the natural weathering exfoliation of seaside rocks, a "chemical weathering" concept for fabricating atom‐thick 2D materials from their bulk counterparts is proposed. It is experimentally demonstrated that chemical weathering‐assisted exfoliation mechanism is a simple and efficient method of preparing atom‐thick MoS2 and WS2 monolayers. These monolayers are difficult to prepare using other approaches. Interestingly, the as‐prepared MoS2 and WS2 monolayers exhibit excellent saturable absorption and mode‐locking properties in all‐solid‐state lasers because of intermediate states resulting from S‐vacancy defects. The obtained passively Q‐switched laser operation with 60 ns pulse width and ultrafast mode locking with 8.6 ps pulse width are promising for all‐solid‐state laser application. Abstract : Inspired by the natural weathering exfoliation of seaside rocks, a "chemical weathering" concept is proposed for fabricating atom‐thick 2D materials from their bulk counterparts. Chemical weathering‐assisted exfoliation is a simple and efficient method of preparing atom‐thick MoS2 and WS2 monolayers. The as‐prepared monolayers exhibit excellent saturable absorption and mode‐locking properties in all‐solid‐state lasers because of intermediate states resulting from S‐vacancy defects.